Highest reported visual acuity after electronic retinal implantation. Issue 7 (28th April 2020) - Cehajic Kapetanovic, Jasmina; Troelenberg, Nicole; Edwards, Thomas L.; Xue, Kanmin; Ramsden, James D.; Stett, Alfred; Zrenner, Eberhart; MacLaren, Robert E.
Abstract: Purpose: To report the highest attained visual acuity with an electronic retinal implant for the treatment of advanced retinal degeneration following a novel intensive period of visual training. Methods: A case study as part of the prospective, international, multi‐centre, interventional clinical trial (ClinicalTrials.gov NCT02720640 and NCT01024803) of patients with the Retina Implant Alpha AMS (Retina Implant AG, Reutlingen, Germany) for advanced retinal degeneration. A patient with subretinal device implanted into worse‐seeing eye with no useful perception of light vision secondary to USH2A retinal degeneration underwent intensive period of visual training. Results: The device remains functional with no safety concerns at 3 years postsurgical implantation, and following visual training, the patient achieved the highest visual acuity so far with an electronic retinal device, with real, digitally unenhanced, reading vision of 0.04 decimal (equivalent to 1.39 LogMAR and 20/500 or 6/150 Snellen). In addition, perception as well as partial identification of obstacles and evaluation of distances was possible in both daylight and night‐time settings. Conclusions: Retinal implants are currently the only available therapy option for advanced retinal degeneration. Visual rehabilitation postimplantation has potential to maximize visual percepts. The novel concept of intensive visual training presented herein shows what is achievable with electronic retinal implants and has implications for other therapeutic options, such as optogenetics, that aim to stimulate remaining inner retinal cells in advanced retinal degeneration.